Inhibition of CFTR-mediated intestinal chloride secretion by nornidulin: Cellular mechanisms and anti-secretory efficacy in human intestinal epithelial cells and human colonoids. - Chamnan Yibcharoenporn; Thidarat Kongkaew; Nichakorn Worakajit; Rungtiwa Khumjiang; Praphatsorn Saetang; Saravut Satitsri; Vatcharin Rukachaisirikul; Chatchai Muanprasat (PLoS ONE)
Secretory diarrhea, a major global health concern, particularly among young children, is often characterized by excessive chloride secretion through the cystic fibrosis transmembrane conductance regulator (CFTR) channel. Nornidulin, a fungus-derived natural product from Aspergillus unguis, has previously been shown to inhibit cAMP-induced Cl- secretion in T84 cells (human intestinal cell lines). However, the cellular mechanism of nornidulin in inhibiting cAMP-induced Cl- secretion and its anti-secretory efficacy is still unknown especially in a human colonoid model, a preclinical model recapitulating intestinal physiology in humans. This research study aimed to examine the mechanism of nornidulin to inhibit cAMP-induced chloride secretion and assess its ability to reduce fluid secretion in both T84 cells and human colonoid models. Apical Cl- current analyses showed that nornidulin inhibited CFTR-mediated Cl- current in T84 cells with IC50 of ~1.5 μM. Nornidulin treatment had no effect on CFTR protein expression. Additionally, the inhibitory effects of nornidulin on CFTR-mediated chloride currents were unaffected by the presence of compounds that inhibit negative regulators of CFTR function, such as protein phosphatases, AMP-activated protein kinases, and phosphodiesterases. Interestingly, nornidulin suppressed the increase in intracellular cAMP levels caused by forskolin, an activator of adenylate cyclases, in T84 cells. Using human colonoid models, we found that nornidulin significantly suppressed the forskolin and cholera toxin-induced fluid secretion, indicating that nornidulin exerted an anti-secretory effect in human intestinal epithelia. Collectively, nornidulin represents a novel class of fungus-derived inhibitors of CFTR-mediated Cl- secretion, potentially making it a promising candidate for the development of anti-secretory treatments.